Genetic Diversity in the Diminazene Resistance-Associated P2 Adenosine Transporter-1 (AT-1) Gene of Trypanosoma evansi - Shoaib Ashraf; Ghulam Yasein; Qasim Ali; Kiran Afshan; Martha Betson; Neil Sargison; Umer Chaudhry (Animals)
Trypanosomes are parasitic protozoa that cause severe diseases in humans and animals. The most important species of Trypanosmes include Trypanosoma evansi and Trypanosoma brucei gambiense. The most well-known human diseases are sleeping sickness in Africa and Chagas disease in South America. The most identified animal diseases include Nagana in the African tsetse fly belt and Surra in South Asia, North Africa, and the Middle East. Surra is caused by Trypanosoma evansi. Diminazene resistance is an emerging threat caused by T. evansi infecting animals. The underlying mechanism of diminazene resistance is poorly understood. Trypanosoma brucei gambiense causes African sleeping sickness. The development of diminazene resistance in Trypanosoma brucei gambiense is associated with the alterations in the corresponding P2 adenosine transporter-1 (AT-1) gene. In the present study, by extrapolating the findings from Trypanosoma brucei gambiense, we analyzed genetic diversity in the P2 adenosine transporter-1 gene (AT-1) from T. evansi to explore a potential link between the presence of mutations in this locus and diminazene treatment in ruminants. We examined T. evansi-infected blood samples collected from goats, sheep, camels, buffalo, and cattle in seven known endemic regions of the Punjab province of Pakistan. Heterozygosity (He) indices indicated a high level of genetic diversity between seven T. evansi field isolates that had resistance-type mutations at codons 178E/S, 239Y/A/E, and 286S/H/I/D/T of the P2 adenosine transporter-1 (AT-1) locus. A low level of genetic diversity was observed in 19 T. evansi field isolates with susceptible-type mutations at codons A178, G181, D239, and N286 of the P2 adenosine transporter-1 (AT-1) locus. Our results on T. evansi warrant further functional studies to explore the relationship between diminazene resistance and the mutations in AT-1.